Peach Brown Rot - Ali Sarkhosh; Shirin Shahkoomahally; Logan Marie Richmond-Cosie; Philip Harmon (EDIS)
Brown rot, caused by Monilinia spp., is one of the most economically harmful fungal diseases for peach and other stone fruit growers worldwide. Under the right conditions, the entire tree’s crop can be completely rotted. Fruit susceptibility fluctuates with the various stages of development; mature fruits are highly susceptible to disease, and fruit infection has the greatest impact on production. This new 7-page publication of the UF/IFAS Horticultural Sciences Department describes the disease cycle, symptoms, and management options available for brown rot in Florida peaches. Written by Ali Sarkhosh, Shirin Shahkoomahally, Logan Marie Richmond-Cosie, and Philip Harmon. https://edis.ifas.ufl.edu/hs1357